2016
DOI: 10.3390/ijms17030425
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Pruritus: The Battle for a Peaceful Night’s Sleep

Abstract: Chronic pruritus is a debilitating condition with numerous etiologies. Many patients suffer from nocturnal pruritus, which can decrease quality of life and affect mortality in hemodialysis patients. Nocturnal pruritus may occur in all sleep stages but is most prevalent in stages N1 and N2. Further research is needed to elucidate the pathophysiology of nocturnal itch, which will aid in the development of tailored management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 70 publications
(89 reference statements)
4
95
1
Order By: Relevance
“…The current study coincides with [30] who found that the majority of participants reported that they had sleeping problems at night. Morever [40] reported that nocturnal pruritus is common in patients under hemodialysis and negatively affects sleep quality. Lack of sleep can have both immediate and long-term effects that lead to medical, social and financial status.…”
Section: Discussionmentioning
confidence: 99%
“…The current study coincides with [30] who found that the majority of participants reported that they had sleeping problems at night. Morever [40] reported that nocturnal pruritus is common in patients under hemodialysis and negatively affects sleep quality. Lack of sleep can have both immediate and long-term effects that lead to medical, social and financial status.…”
Section: Discussionmentioning
confidence: 99%
“…Besides dermatitis, visual and auditory stimulation suggestive of itching, such as the skin scratching sound, induces itching and becomes prominent in AD . Imbalances between the sympathetic nerve system and the parasympathetic nerve system, emotional and psychogenic factors, and disturbances in life rhythm are associated with onset and worsening of itch …”
Section: Chapter Imentioning
confidence: 99%
“…29,30 Imbalances between the sympathetic nerve system and the parasympathetic nerve system, emotional and psychogenic factors, and disturbances in life rhythm are associated with onset and worsening of itch. 31,32 Genetic factors. Some genes have been described as candidate genes associated with AD: CTLA4, IL18, TLR9, CD14, CARD4, PHF11, TLR2, SCCE, MCC, IL4R, GM-CSF, TIM1, CARD15, GSTT1, SPINK5, SCYA11, TGFb1, IL-13, RANTES, IL4, and FCER1B 13 .In addition, 2q12 (IL1RL1/IL18R1/IL18RAP), 3q21.33 (GLB1), 3q13.2 (CCDC80), 6p21.3 (MHC region), 7p22 (CARD11), 10q21.2 (ZNF365), 11q15.4 (OR10A3/NLRP10), 20q13 (CYP24A1/PFDN4) have been reported to be an AD-related region based on genome-wide linkage analysis from Japanese samples.…”
Section: Pathophysiologymentioning
confidence: 99%
“…There is undoubtedly a psychological component to nocturnal pruritus as well. Patients with chronic itching tend to have higher levels of stress and depression, which are both associated with difficulty sleeping . It is likely that poor sleep hygiene also plays a role.…”
Section: Pathophysiologymentioning
confidence: 99%
“…GABAergics (gabapentin and pregabalin) are structural analogs of gamma‐aminobutyric acid (GABA) that improve sleep quality through their sedative properties. They have been shown to reduce pruritus secondary to neural hypersensitization, which is commonly seen in patients with AD, but no studies have evaluated their effectiveness in relieving nocturnal itching or improving sleep quality in children with nocturnal pruritus. Side effects of gabapentinoids include fatigue, dizziness, blurred vision, and weight gain …”
Section: Systemic Therapiesmentioning
confidence: 99%